Gender Differences in the Information Systems Managerial Ranks: An Assessment of Potential Discriminatory Practices - Truman, Gregory E.; Baroudi, Jack J. (MIS Quarterly, 1994)
This paper examines the extent to which gender discrimination is a force affecting the senior managerial ranks of the information systems (IS) occupation. While the employment trends of women in the IS occupation is encouraging, data are presented that suggest that IS may not be immune to the problems of gender discrimination. Analyzing data gathered by the Society for Information Management (SIM), a problem suggestive of discriminatory practices was found. Women receive lower salaries than men even when job level, age, education, and work experience are controlled.